Consumer Justice: A Symbol of Economic Prosperity and Social Progressiveness - Roy, Subir Kumar (Faculty of Law, Hasanuddin University, 2016)
It is well recognized fact that consumer confidence and trust in a well functioning market for financial services promotes financial stability, growth efficiency and innovation over the long term. So protection of the interest of consumers is not merely an ethical or humanitarian issue rather it is also an issue of economy. Consumer protection demands for setting of minimum quality specification and safety standards for goods and services to curb unfair trade practices. So far the international norms are concerned it effectively contains the Bill of Rights of Consumers which help them across the globe to effectively protect their interests. Keeping in consideration about the poor bargaining position of the consumers and with an aim to ensure consumers to access non-hazardous products United Nation issued Guidelines for Consumer Protection, 1985, expanded again in 1999. The consumer justice is a facet of socio-economic justice and emanates from the basic philosophy of the Indian constitution i.e. to do justice and to strengthen the standard and status of the people of this country. It has been discussed in this article in an elaborate way about the various provisions of the Constitution and all the legislations which addresses the issues of consumers and resolve to protect their interests. But still the exploitation of Indian consumers by the dishonest traders and service providers become a routine matter and this article also scanned the reasons for the same and also provides suggestions to ameliorate the conditions of consumers. This paper is based on qualitative analysis of the information mainly obtained from secondary sources such as different books and journals as referred over here, Policy documents, existing laws, reports of United Nations, important judgments and observations of Judiciary etc.